KEMAMPUAN PESERTA DIDIK KELAS IV MEMBUAT KARYA MONTASE DALAM PEMBELAJARAN SENI BUDAYA DAN PRAKARYA DI SEKOLAH DASAR - Lora Devian; Desyandri; Farida Mayar (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The purpose of this study was to determine the ability of class IV students to make montage works in SBdP learning at SDN 09 Kampung Melayu, Ampek Nagari District, Agam Regency, West Sumatra and the obstacles faced by class IV students to make montage works in SBdP learning at SDN 09 Kampung Melayu. The population in this study were all fourth grade students, totaling 22 people.Data collection techniques used are interview, test, and documentation techniques. The research data was processed by descriptive data analysis techniques. The results of the study show that: 1) The ability of students to make montage artworks in learning Cultural Arts and Crafts at SDN 09 Kampung Melayu is categorized as quite good, this is evidenced by the results of the assessment of students' montage artworks with a percentage of 54.55% who get grades. 70-79 (enough category) and as many as 45.45% of students who get a score of 80-89 (good category), it can be concluded that the average value of students can reach the KKM (Minimum Completeness Criteria). 2) The obstacles faced by class IV students in making montage artworks are that students do not know about montage artworks so that they experience a little difficulty in the work process and the limited time given, as well as the absence of special guidance or training for students in making montage artwork.